О построении основ механики нанокомпозитов (обзор) - Гузь, А.Н.; Рущицкий, Я.Я. (Прикладная механика, 2011)
A general view on mechanics of nanocomposite materials is stated, which allows to formulate a system of approaches and methods of analysis in this area. A place of mechanics in studying the materials and the dividing of mechanics on macromechanics, mesomechanics, micromechanics and nanomechanics structural levels are discussed. A short-form historical sketch of development in technology of making the nanomaterials is expounded. The examples of different nanotechnologies and nanomaterials are given. The typical nanomaterials and their properties are described. Severally the matrixes and reinforcing elements of nanocomposite materials as well as their properties are considered. A variant of classification of nanocomposite materials is proposed. A special attention is drawn to modeling in structural mechanics of composites, principles of continualization and homogenization, edge and near-the-surface effects, validity ranges of continuum approach, bilateral estimates. Two basic models are discussed within the framework of the basic approch as the collection of concepts, models and problem statements, the development of method of analysis and obtaining the basic results adequate to mechanical phenomena in nanocomposites. The presented material corresponds, in the main, to the book Guz A.N., Rushchitsky J.J., Guz I.A., Introduction to Mechanics of Nanocomposites, Kiev, S.P.Timoshenko Institute of Mechanics, 2010, 398 p.